Novel Er 3+ /Ho 3+ codoped glassceramic fibers for broadband tunable midinfrared fiber lasers - Kang,S; Yu,H; Ouyang,T; Chen,Q; Huang,X; Chen,Z; Qiu,J; Dong,G (Journal of the American Ceramic Society, 2018)
Abstract It is well recognized that a widely wavelengthtunable midinfrared ( MIR ) fiber laser plays an important role in the development of compact and efficient coherent sources in the MIR range. Herein, the optimizing Er/Ho ratio for enhancement of broadband tunable MIR emission covering 2.62.95 μm in the Er 3+ /Ho 3+ codoped transparent borosilicate glassceramic ( GC ) fibers containing Na YF 4 nanocrystals under 980 nm excitation was investigated. Specifically, the obtained GC fibers with controllable crystallization and well fsdmaintained structures were prepared by the novel meltintube approach. Owing to the effective energy transfer between Er 3+ and Ho 3+ after crystallization, the 2.7 μm MIR